에너지 하베스팅 네트워크에서 물리계층 보안을 향상시키기 위한 파워 분할 기반의 아날로그 네트워크 코딩 - 이기송(Kisong Lee); 최현호(Hyun-Ho Choi) (한국정보통신학회논문지, 2017)
Recently, RF energy harvesting, in which energy is collected from the external RF signals, is considered as a promising technology to resolve the energy shortage problem of wireless sensors. In addition, it is important to guarantee secure communication between sensors for implementing Internet-of-Things. In this paper, we propose a power splitting-based network analog coding for maximizing a physical layer security in 2-hop networks where the wireless-powered relay can harvest energy from the signals transmitted by two sources. We formulate systems where two sources, relay, and eavesdropper exist, and find an optimal power splitting ratio for maximizing the minimum required secrecy capacity using an exhaustive search. Through simulations under various environments, it is demonstrated that the proposed scheme improves the minimum required secrecy capacity by preventing the eavesdropper from overhearing source signals, compared to the conventional scheme. 외부의 RF 신호로부터 전력을 수집하는 RF 에너지 하베스팅은 무선 센서의 전원 부족 문제를 해결하는 기술로써 최근 큰 관심을 받고 있다. 뿐만 아니라, 사물 인터넷의 구현을 위해서는 센서 간의 보안 통신을 보장하는 것 역시 중요하다. 본 논문에서는 두 source로부터 전송되는 신호로부터 에너지 하베스팅이 가능한 relay가 존재하는 2-hop 네트워크에서 물리계층 보안을 최대화하기 위한 파워 분할 기반 네트워크 아날로그 코딩을 제안한다. 두 source, relay, eavesdropper가 존재하는 시스템을 수학적으로 모델링하고, exhaustive search를 통해 최소 요구 보안 용량을 최대화 할 수 있는 최적의 파워 분할 비율을 찾았다. 다양한 환경에서 시뮬레이션을 통해 제안 방안은 기존 방안에 비해 eavesdropper에서의 도청을 막아 최소 요구 보안 용량을 개선함을 보인다.